2012
DOI: 10.1002/chem.201103675
|View full text |Cite
|
Sign up to set email alerts
|

Dendron‐Containing Tetraphenylethylene Compounds: Dependence of Fluorescence and Photocyclization Reactivity on the Dendron Generation

Abstract: The synthesis and characterization of four dendron-containing tetraphenylethylenes (TPEs), 1(1)-1(4), were synthesized, along with a TPE compound that contained four OCH(2) Ph groups (referred to as 1(0)) for comparison. Photophysical studies revealed that the TPE core became emissive after linking dendrons onto its periphery. Moreover, the fluorescence intensity was significantly enhanced when high-generation dendrons were linked onto the TPE core; the fluorescence intensity increased in the following order: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 91 publications
(43 reference statements)
3
47
0
Order By: Relevance
“…This result is different from the previous reports, in which phenyl rings are mainly involved in the photocyclodehydrogenation reaction. [ 32,39,40 ] c -TPP3M is less conjugated than o -TPP3M, as revealed by its bluer absorption maximum (Table 1 ). However, it shows a much effi cient light emission in solution with a Φ F as high as 69% due to the activation of the RIM process by the photocyclodehydrogenation reaction.…”
Section: Communicationmentioning
confidence: 98%
See 3 more Smart Citations
“…This result is different from the previous reports, in which phenyl rings are mainly involved in the photocyclodehydrogenation reaction. [ 32,39,40 ] c -TPP3M is less conjugated than o -TPP3M, as revealed by its bluer absorption maximum (Table 1 ). However, it shows a much effi cient light emission in solution with a Φ F as high as 69% due to the activation of the RIM process by the photocyclodehydrogenation reaction.…”
Section: Communicationmentioning
confidence: 98%
“…The pyridinium ring is thus comparatively more reactive than the other phenyl rings in the excited state, making its preferred participation in the photocyclodehydrogenation reaction. If the photocyclodehydrogenation of o -TPP3M occurs in a general way, [ 32,39,40 ] a product, named as c -TPP3M(b), will be obtained. Its structure was simulated, optimized, and provided in Figure 2 e. Comparing c -TPP3M with c -TPP3M(b) in their most optimized confi guration, it was found that c -TPP3M was thermodynamically more stable than c -TPP3M(b) with 21.47 kJ mol −1 lower energy.…”
Section: Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…To tackle our challenge, we constructed dendrimers that were multifunctionalized at the periphery with TPE and, in a step, photoconvert some of the TPE to DPP units. The fundamentals of photoinduced conversion of TPE to DPP are well established, and the conversion is controlled by the irradiation time and solvent. We used irradiation time to control the conversion of TPE to DPP in order to access heterofunctional dendrimers that were dual emissive.…”
Section: Introductionmentioning
confidence: 99%